2008
DOI: 10.1375/twin.11.5.505
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry, Carbohydrate and Lipid Metabolism in the East Flanders Prospective Twin Survey: Linkage of Candidate Genes Using Two Sib-Pair Based Variance Components Analyses

Abstract: I nsulin resistance and obesity are underlying causes of type 2 diabetes and therefore much interest is focused on the potential genes involved. A series of anthropometric and metabolic characteristic were measured in 240 MZ and 112 DZ twin pairs recruited from the East Flanders Prospective Twin Survey. Microsatellite markers located close to ABCC8, ADIPOQ, GCK, IGF1, IGFBP1, INSR, LEP, LEPR, PPARγ and the RETN gene were genotyped. Univariate single point variance components linkage analyses were performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
5
0
1
Order By: Relevance
“…In humans, the levels of IGFBP1 showed a suggestive association with fat mass (Souren et al, 2008) and a study performed with children demonstrated that IGFBP1 and IGFBP3 are inversely related to adiposity (Toledo-Corral et al, 2008). This evidence led us to point to IGFBP3 as a candidate gene to influence fat thickness in Canchim population, but our hypothesis was not supported by the analysis performed (Table 1).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In humans, the levels of IGFBP1 showed a suggestive association with fat mass (Souren et al, 2008) and a study performed with children demonstrated that IGFBP1 and IGFBP3 are inversely related to adiposity (Toledo-Corral et al, 2008). This evidence led us to point to IGFBP3 as a candidate gene to influence fat thickness in Canchim population, but our hypothesis was not supported by the analysis performed (Table 1).…”
Section: Resultsmentioning
confidence: 75%
“…Ballard and colleagues (1988) cloned and characterized six IGFBPs in humans and rodents, which are believed to be similar to those of domestic animals. Levels of IGFBPs were related to fat mass in humans (Souren et al, 2008;Toledo-Corral et al, 2008). The development and differentiation enhancing factor 1 gene (DDEF1) is located within the region harboring QTLs for fat deposition traits on BTA14.…”
Section: Introductionmentioning
confidence: 99%
“…Adiposity and body fat distribution are both heritable traits, while the heritability of body fat distribution is distinct from that of overall adiposity [40], [41], [42], [43]. Body fat distribution is divided into two general types: android (upper body or ‘apple’ shape) and gynoid (lower body or ‘pear’ shape), where an android fat distribution is more commonly associated with adverse metabolic outcomes [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, we included phenotypic data of MZ twins, as this will result in more accurate variance components estimates. For birth weight, the inclusion of phenotypic data of MZ monochorionic twins results in a reduced power to detect a QTL, 35 therefore only phenotypic data of the MZ dichorionic pairs were incorporated. Estimates of the variance component associated with the QTL were obtained using the pi-hat approach, in which the covariance due to the QTL for a sib-pair is modelled as a function of the proportion of alleles shared IBD.…”
Section: Conventional Linkage Analysismentioning
confidence: 99%